A Bibliometric analysis of single mothers - Changyan, Cai; Beatrice Lim; Salmah Topimin; Noor Fzlinda Fabeil; Haslinda Hasan (Penerbit Universiti Kebangsaan Malaysia, 2023)
In recent years, there has been an increasing amount of research on single mothers internationally. This article analyzes 1543 research papers on single mothers from Web of Science database using CiteSpace literature analysis software. The study found that research on single mothers covers 79 countries globally, forming a close and comprehensive cooperative network between them. The North American region, including the United States and Canada, is a core research force in the field of single mothers. The top 15 research institutions produced more than 30 papers each, with the University of California System ranking first with a total of 72 papers. The journal with the most publications was the Journal of Marriage and Family, with a total of 44 papers. There were 8 authors who published more than 10 papers, with Herbst CM having the most with 16 papers. The frequency of citations for research on single mothers has shown a significant increasing trend in recent years, with a total of 36,624 citations, an average of 23.74 citations per paper, and an h-index of 83. Through the analysis of clustering networks and high-frequency keywords, the research hotspot on single mothers mainly focuses on four aspects: the psychological health of single mothers, the economic and employment status of single mothers, the children of single mothers, and the social support of single mothers.